2019
DOI: 10.1038/s41433-019-0443-x
|View full text |Cite
|
Sign up to set email alerts
|

Visual performance of an extended depth of focus intraocular lens for treatment selection

Abstract: Purpose To evaluate the visual performance of an extended depth of focus (EDOF) intraocular lens (IOL) for patient selection. Methods This prospective non-comparative case series evaluated fifty-two eyes (26 patients) after bilateral implantation of the Tecnis Symfony IOL. Exclusion criteria were previous ocular surgeries, corneal astigmatism of >1.5 diopter, and ocular pathologies or corneal abnormalities. Uncorrected (UCVA) and distance-corrected (DCVA) visual acuity (VA) in 4 m, 80 cm, 60 cm and 40 cm (logM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 33 publications
7
57
0
2
Order By: Relevance
“…The TECNIS Symfony EDOF IOL (ZXR00) has shown to offer good far, intermediate and near visual outcomes, and better outcomes especially for far and intermediate visual acuities, but with a few limitations in near visual acuity [ 15 ]. However, compared with other multifocal IOLs, ZXR00 results in fewer postoperative photic phenomena [ 16 ]. In this study, with the strength in photic phenomena, the limitation of decreased near visual acuity in EDOF IOLs was overcome by mix-and-match implantation of a DMF IOL in the nondominant eye.…”
Section: Discussionmentioning
confidence: 99%
“…The TECNIS Symfony EDOF IOL (ZXR00) has shown to offer good far, intermediate and near visual outcomes, and better outcomes especially for far and intermediate visual acuities, but with a few limitations in near visual acuity [ 15 ]. However, compared with other multifocal IOLs, ZXR00 results in fewer postoperative photic phenomena [ 16 ]. In this study, with the strength in photic phenomena, the limitation of decreased near visual acuity in EDOF IOLs was overcome by mix-and-match implantation of a DMF IOL in the nondominant eye.…”
Section: Discussionmentioning
confidence: 99%
“…12 The IOL also adds −0.27μm of spherical aberration to counterbalance net positive spherical aberration from the cornea. 13 Kohnen et al 14 recently reported that average patient uncorrected visual acuity was 0.22 logMAR or better at 40cm, 60cm, 80cm, and distance. Good performance with the Tecnis Symfony IOL has also been reported in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…some limitations for near vision (14). However, compared with other multifocal IOLs, ZXR00 results in fewer postoperative photic phenomena (15). In this study, with the strength in photic phenomena, the limitation of decreased near visual acuity in EDOF IOLs was overcome by mix-and-match implantation of a DMF IOL in the non-dominant eye.…”
Section: Discussionmentioning
confidence: 64%